Tantangan Hukum Aset Kripto Terhadap Penggunaan Telegram Wallet di Indonesia - Gunawan, Imam (Officium Notarium, 2024)
Technological innovation, especially in the economic sector, has introduced cryptocurrency as a digital payment tool that has replaced physical money and the use of Telegram Wallet. This article examines the legal challenges faced in Indonesia in the use of Telegram Wallet which functions as a cryptocurrency transaction platform even though cryptocurrency in Indonesia was initially only recognized as a futures commodity asset, not as a means of payment. The purpose of the study is to identify the legal problems of crypto assets contained in the Telegram application, namely wallets, both in terms of potential and the resulting impacts. The research method used is normative research with a legislative approach and a conceptual approach. Data were collected through literature studies covering primary legal materials and secondary legal materials. The discussion of this study highlights the legal complexities related to Telegram Wallet, starting from licensing issues as a physical trader of crypto assets, intervention of the role of social media with crypto asset transaction platforms, and legal protection, both consumer protection and personal data protection. The results of the study are that the legal challenges of crypto assets faced will provide problems in the future because regulations are inadequate, both Telegram's position as an organizer of an electronic social media system as an organizer of crypto asset trading and legal protection for users. Therefore, there is a need for recommendations for better regulatory integration and strengthening of legal supervision to avoid potential misuse and crimes that occur in crypto asset transactions on Telegram Wallet.Keywords: Crypto Assets, Cryptocurrency, Telegram, Telegram Wallet AbstrakInovasi teknologi khususnya dalam bidang perekonomian telah memperkenalkan cryptocurrency sebagai alat pembayaran digital menggantikan uang fisik serta penggunaan Telegram Wallet. Penelitian ini mengkaji tantangan hukum yang dihadapi di Indonesia dalam penggunaan Telegram Wallet yang berfungsi sebagai platform transaksi cryptocurrency meskipun cryptocurrency di Indonesia awalnya hanya diakui sebagai aset komoditi berjangka bukan sebagai alat pembayaran. Tujuan penelitian adalah mengidentifikasi masalah hukum aset kripto yang terdapat pada aplikasi Telegram, yaitu wallet baik secara potensi maupun dampak yang dihasilkan. Metode penelitian yang digunakan adalah penelitian normatif dengan pendekatan perundang-undangan dan pendekatan konseptual. Data dikumpulkan melalui studi kepustakan yang mencakup bahan hukum primer dan bahan hukum sekunder. Pembahasan penelitian ini menyoroti kompleksitas hukum terkait Telegram Wallet mulai dari masalah perizinan sebagai pedagang fisik aset kripto, intervensi peran media sosial dengan platform transaksi aset kripto, dan pelindungan hukum baik pelindungan konsumen dan pelindungan data pribadi. Hasil penelitian adalah tantangan hukum aset kripto yang dihadapi akan memberikan problematika di masa depan karena regulasi belum memadai baik kedudukan Telegram sebagai penyelenggara sistem elektronik media sosial sebagai penyelenggara perdagangan aset kripto maupun pelindungan hukum bagi para pengguna. Oleh karena itu, perlunya rekomendasi dalam integrasi regulasi yang lebih baik dan penguatan pengawasan hukum agar menghindari potensi penyalahgunaan dan kejahatan yang terjadi dalam transaksi aset kripto di Telegram Wallet.Kata kunci: Aset Kripto, Cryptocurrency, Telegram, Telegram Wallet